Zinc intake ameliorates intestinal morphology and oxidative stress of broiler chickens under heat stress - Hu, Ping; Li, Kaiqi; Peng, Xiaoxu; Yao, Tongjia; Zhu, Chuyang; Gu, Haotian; Liu, Hao-Yu; Sun, Ming-an; Hu, Yun; Ennab, Wael; Luo, Xugang; Cai, Demin (Frontiers in Immunology, 2024)
Zinc (Zn), an essential trace element for poultry, plays a crucial role in promoting growth, improving feed conversion efficiency, enhancing antioxidant activity, and preventing disease. This study investigated the impact of different levels and sources of dietary Zn supplementation on the growth performance, intestinal morphology and antioxidant activity of broiler chickens under heat stress conditions. In this experiment, 1024 Xueshan chickens were divided into eight groups and subjected to heat stress conditions with different levels of Zn supplementation (30 mg/kg, 60 mg/kg, and 90 mg/kg) using organic or inorganic sources. Our findings indicated that dietary Zn supplementation significantly increased the feed-to-weight ratio of broilers during the experimental period under heat stress. Moreover, Zn supplementation positively increased the villus height and villus width in the jejunum and ileum at 74 and 88 days old, with the 60 and 90 mg/kg groups outperforming other groups, and organic Zn was more effective than inorganic Zn. Furthermore, Zn supplementation significantly increased serum antioxidant levels, with higher superoxide dismutase (SOD), malondialdehyde (MDA), and glutathione peroxidase (GSH-px) activities, and organic Zn was more effective than inorganic Zn. This study concludes that Zn supplementation is beneficial in mitigating the detrimental impacts of heat stress on broilers. The findings suggest that employing Zn as a strategy can enhance productivity in the poultry industry by positively influencing intestinal morphology and bolstering antioxidant activity to counteract potential stress.